The Incidence of Infection After Early Closure of Evulsive Facial Wounds - Hosseini- (Tehran University of Medical Sciences, 2000)
The aim of this study was to evaluate the incidence of postoperative wound dehiscence and"ninfection after early closure of evulsive facial wounds. This treatment was conducted on 28 male patients"nwith evulsive facial wounds. The formation of these evulsive wounds was due to the rupture of"ntemporary cavitation caused by high and extra high velocity messiles. All patients with average age of 18"nyears old were treated 24-48 hrs afire accidents at base hospitals (1988-1990)."nPrimary healing was achieved in 24 subjects from 7 tO 15 days after the standard operation. Wound"ndehiscences and bacterial infections were observed in 4 subjects."nThe conclusion can be made from the results is that the early closure of evulsive facial wounds may"nreduce the rate of wound dehiscence and infection because of high vascularity in this area.